Model validity and risk of bias in randomised placebo-controlled trials of individualised homeopathic treatment. (April 2016) - Mathie, Robert T.; Wassenhoven, Michel Van; Jacobs, Jennifer; Oberbaum, Menachem; Frye, Joyce; Manchanda, Raj K.; Roniger, Helmut; Dantas, Flávio; Legg, Lynn A.; Clausen, Jürgen; Moss, Sian; Davidson, Jonathan R.T.; et al.
Abstract: Background: To date, our programme of systematic reviews has assessed randomised controlled trials (RCTs) of individualised homeopathy separately for risk of bias (RoB) and for model validity of homeopathic treatment (MVHT). Objectives: The purpose of the present paper was to bring together our published RoB and MVHT findings and, using an approach based on GRADE methods, to merge the quality appraisals of these same RCTs, examining the impact on meta-analysis results. Design: Systematic review with meta-analysis. Methods: As previously, 31 papers (reporting a total of 32 RCTs) were eligible for systematic review and were the subject of study. Main outcome measures: For each trial, the separate ratings for RoB and MVHT were merged to obtain a single overall quality designation ('high', 'moderate, "low", 'very low'), based on the GRADE principle of 'downgrading'. Results: Merging the assessment of MVHT and RoB identified three trials of 'high quality', eight of 'moderate quality', 18 of 'low quality' and three of 'very low quality'. There was no association between a trial's MVHT and its RoB or its direction of treatment effect ( P  > 0.05). The three 'high quality' trials were those already labelled 'reliable evidence' based on RoB, and so no change was found in meta-analysis based on best-quality evidence: a small, statistically significant, effect favouring homeopathy. Conclusion: Accommodating MVHT in overall quality designation of RCTs has not modified our pre-existing conclusion that the medicines prescribed in individualised homeopathy may have small, specific, treatment effects.